Extension territoriale des mégalithes au Cameroun : foyers éteints, cultures vivantes et arts environnementaux - Narcisse Santores Tchandeu (OpenEdition, 2017)
From the perspective of a general inventory of megalithism in Cameroon, an interdisciplinary team has been studying since 2006 the origins, forms and territorial distribution of these stone structures. While in some areas such as the Mandara Mountains and the upper Benoue Valley, this type of production participates in a still alive ethnology, in other regions such as Adamawa, islamization has precipitated a rapid abandonment of megalithic traditions, yet classified among the oldest known in Cameroon. This is reflected in the Grassland where construction traditions have gradually disappeared under the influence of westernization, although the ancient heritage still serves as an active reference point for current ritual activities. Historical archaeology, comparative ethnology, ethnolinguistics, phenomenology of image and ethnobotany are all methodological approaches that have enabled us to trace the origins of megaliths, compare their technical manufacturing processes, grasp the sense that the elements take, both in languages, visual perceptions and collective memories, and in a cosmology where the plant kingdom occupies a fundamental place.